Attentional biases and time course of emotion processing in depression - Bastidas, Stephanie P., author; Troup, Lucy J., advisor; Henry, Kimberly L., committee member; Draper, Bruce A., committee member (Colorado State University. Libraries, 2014)
Depressive mood is associated with differential patterns in emotion processing, but it is unclear which stages of processing differ in depressed individuals. The current study explored the nature of biases in early vs. late components of attention. Experiment 1 examined attention biases in orienting to and disengaging from positive and negative emotional stimuli behaviorally. Depressed participants presented greater overall biases than controls in the dot-discrimination but not in the dot-detection task. Positive and negative affect were associated with greater orienting bias and reduced disengaging bias for happy faces in the detection task and smaller bias for happy faces and greater for sad faces in the discrimination task. Experiment 2 explored differences in the time course of emotion processing, with focus on early P3 component differences during implicit and explicit processing. Results showed greater P3 for happy than neutral trials over midline frontal electrodes and the opposite pattern over parietal electrodes in depressed but not control participants during implicit processing. P3 was slower in depressed than controls during explicit processing over lateral sites. Midline electrodes showed slower P3 for happy than neutral during implicit processing and for sad than neutral during explicit, independent of group. Results suggest the presence of attentional biases in depressed individuals independent of emotion. These biases might be better reflected during intentional than incidental emotion processing. Future study is needed to fully understand the relationship of emotion processing for different degrees of depressive symptoms, emotions, and with regard to other modalities of intention in emotion processing.
Keywords: attention; cognitive bias; depression; emotion; event-related potential; P3